(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Aim: To evaluate the expression of CD133 and OCT 4 in Oral Squamous Cell Carcinoma. Materials and methods: The study included a total of 50 samples of Archival tissue blocks that were categorised as control and cases (Oral squamous cell carcinoma) and further as Well-differentiated & Moderately squamous cell carcinoma. The sections of both Group I and group II were subjected to Immunohistochemical staining using CD133 antibody and anti-Oct-4 antibody. The cells were counted and the data obtained were compared for the significance keeping p<0.05 as significant. Results: Statistical significance is observed on the correlation of CD133 and OCT 4 expression when the mean number of positive cells is compared between the control and study groups. A high statistical significance is observed on the correlation of CD133 and OCT 4 expression when the mean number of positive cells is compared in normal mucosa and moderately differentiated Squamous cell carcinoma. Conclusion: The quantitative expression of CD133 and OCT 4 increased from normal mucosa to the well-differentiated variation of oral squamous cell carcinoma, and subsequently to the moderately differentiated variant, suggesting that CD133 and OCT 4 plays a role in determining the prognosis of oral squamous cell carcinoma patients.